Pengaruh Literasi Keuangan terhadap Keputusan Investasi Generasi Z dengan Moderasi Penguasaan Media Teknologi - Made Wedaswari; Ahmad Dzakiyuddin; Shinta Nastitie Komalasari; Yoga Pratama Nugroho; Gustita Arnawati Putri; Astrid Nur Aini; Hanyfa Ayu Anggrainy; Ariyani Wahyu Wijayanti (Yayasan Literasi Ilmiah Indonesia, 2026)
Purpose: This study aims to analyze the effect of financial literacy on investment decisions of Generation Z and to examine the moderating role of media technology mastery. Method: This study uses a quantitative explanatory approach. Data were collected through questionnaires from 150 Generation Z respondents in Solo Raya who have investment experience. The data were analyzed using Moderated Regression Analysis (MRA) to test direct and moderating effects. Finding: The results indicate that financial literacy has a significant effect on investment decisions, showing that individuals with better financial understanding tend to make more rational decisions. Media technology mastery does not have a direct effect on investment decisions. However, it significantly moderates the relationship between financial literacy and investment decisions, strengthening the influence of financial literacy. Novelty: This study emphasizes media technology mastery as a moderating variable, highlighting that technology strengthens the impact of financial literacy rather than directly influencing investment decisions.